SISTEM REKOMENDASI PEMESANAN OBAT BERBASIS WEB BERDASARKAN TANGGAL KADALUARSA MENGGUNAKAN METODE FIRST EXPIRED FIRST OUT (STUDI KASUS : APOTEK CITO) - Aufa Sarifatun Nisa (Universitas Lampung, 2026)
Apotek Cito still manages its pharmaceutical inventory using spreadsheets, resulting in difficulties in stock monitoring, expiration date management, and determining drug ordering priorities. These conditions may lead to stock accumulation and financial losses caused by drugs approaching their expiration dates. This study aims to design and develop a Web-Based Drug Ordering Recommendation System by implementing the First Expired First Out (FEFO) method. The system was developed using the Prototype model, which includes the stages of requirements analysis, prototype development, evaluation, implementation, testing, and system maintenance. The results show that the developed system is capable of managing drug data, monitoring stock levels and expiration dates in real time, and providing priority recommendations based on expiration dates and available stock quantities. The testing results indicate that all system functions operate properly and achieved a user acceptance rate of 90.67%, which falls into the excellent category. Therefore, the developed system can help improve the effectiveness of pharmaceutical inventory management and minimize the risk of losses caused by expired drugs at Apotek Cito